Effect of left ventricular ejection fraction on the prognostic impact of chronic total occlusion in a non-infarct-related artery in patients with acute myocardial infarction. (April 2021) - Ito, Hiromasa; Masuda, Jun; Kurita, Tairo; Ida, Mizuki; Yamamoto, Ayato; Takasaki, Akihiro; Takeuchi, Tetsushiro; Sato, Yuichi; Omura, Takashi; Sawai, Toshiki; Tanigawa, Takashi; Ito, Masaaki; et al.
Abstract: Background: Chronic total occlusion (CTO) in a non-infarct-related artery (IRA) in patients with acute coronary syndrome (ACS) is associated with a poor prognosis. However, whether the prognostic impact of non-IRA CTO differs according to left ventricular ejection fraction (LVEF) is unclear. Methods and results: A total of 2060 consecutive acute myocardial infarction (AMI) patients who underwent primary percutaneous coronary intervention (PCI) were classified into 2 groups according to their LVEF (reduced EF: LVEF < 50%, preserved EF: LVEF ≥ 50%) and further subdivided according to the presence of concomitant non-IRA CTO. In the reduced EF group, patients with CTO had a higher 1-year all-cause death rate (20.3% vs. 34.3%, P = 0.001) and major adverse cardiac event rate (MACE: 19.6% vs. 39.6%, P < 0.001) compared to those without CTO, but they were similar between patients with and without CTO in the preserved EF group. Non-IRA CTO was an independent predictor of all-cause death (HR 1.58, 95% CI 1.06–2.33, P = 0.02) and MACE (HR 1.67, 95% CI 1.14–2.46, P = 0.009) only in the reduced EF group. In addition, the outcomes of successful CTO-PCI seemed to be similar to those without CTO in the reduced EF group. Conclusions: CTO in a non-IRA may contribute to a poor prognosis only in AMI patients with reduced LVEF.